Monopsony Power, Offshoring, and a European Minimum Wage - Hartmut Egger; Udo Kreickemeier; Jens Wrona (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper sets up a two-country model of offshoring with monopolistically competitive product and monopsonistically competitive labour markets. In our model, an incentive for offshoring exists even between symmetric countries, because shifting part of the production abroad reduces local labour demand and allows firms to more strongly execute their monopsonistic labour market power. However, offshoring between symmetric countries has negative welfare effects and therefore calls for policy intervention. In this context, we put forward the role of a common minimum wage and show that the introduction of a moderate minimum wage increases offshoring and reduces welfare. In contrast, a sizable minimum wage reduces offshoring and increases welfare. Beyond that, we also show that a sufficiently high common minimum wage cannot only eliminate offshoring but also inefficiencies in the resource allocation due to monopsonistic labour market distortions in closed economies.
Keywords: F12; F16; F23; J42; 330; offshoring; minimum wage; welfare effects